2013
DOI: 10.1002/phy2.95
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dipeptidyl peptidase-4 inhibition in an animal model of experimental asthma: a matter of dose, route, and time

Abstract: The CD26-associated enzymatic activity of dipeptidyl peptidase-4 (DPP4) as well as the recruitment of CD26+ T cells increase under allergic airway inflammation. Furthermore, genetic deficiency of CD26/DPP4 exerts protective effects in experimental asthma. Therefore, CD26/DPP4 might represent a novel therapeutic target in asthma. To study the effects of pharmacological inhibition of DPP4 on allergic airway inflammation the DPP4-inhibitor isoleucine thiazolidide was tested using different doses at different time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Our results confirm our hypothesis that the application of DPP4 inhibitors leads not only to an increased synthesis of SP in allergic‐like airway inflammation (Stephan et al . ) but also partially in healthy control lungs (Table ) however at former time points (Figs ) than in asthma‐induced rats (Stephan et al . ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our results confirm our hypothesis that the application of DPP4 inhibitors leads not only to an increased synthesis of SP in allergic‐like airway inflammation (Stephan et al . ) but also partially in healthy control lungs (Table ) however at former time points (Figs ) than in asthma‐induced rats (Stephan et al . ).…”
Section: Discussionmentioning
confidence: 93%
“…Surprisingly, pharmacological inhibition of DPP4 in asthmatic rats resulted in an significant increase of all SPs at the mRNA level (Stephan et al . ). Therefore, the question came up if these inhibitors would influence also the surfactant protein expression in healthy DPP4/CD26 + rats in comparison with positive controls such as glucosteroides or negative controls such as inactive inhibitors.…”
mentioning
confidence: 97%
“…Indeed, Stephan et al have shown that continuous systemic inhibition of DPP-4 mediated by oral administration exacerbates airway inflammation in an experimental model of asthma. Conversely, topical inhibition was effective and given its potential impact on this prevalent and significant respiratory disease, further research in humans is merited [58].…”
Section: Expert Opinionmentioning
confidence: 99%
“…DPP4 inhibition has effects on airway inflammation in animal models that depend on the route of administration (oral, aerosolized, topical). 39 Studies of DPP4 in human airway inflammation are limited. Other potential biomarkers of type 2 inflammation include urinary bromotyrosine (BrTyr), 40,41 monocyte chemoattractant protein-4 (MCP4), and eotaxin-2.…”
Section: Other Biomarkers Of Type 2 Inflammationmentioning
confidence: 99%